Infection-derived lipids elicit an immune deficiency circuit in arthropods - Dana K. Shaw (Nature Portfolio, 2017)
The insect IMD signalling pathway detects invading pathogens. Here the authors show that ticks have an alternative IMD system that lacks peptidoglycan receptors, IMD and FADD, and is instead reliant on interaction of the E3 ligase XIAP with the E2 conjugating enzyme Bendless.